In situ self-doped biomass-derived porous carbon as an excellent oxygen reduction electrocatalyst for fuel cells and metal–air batteries. Issue 25 (15th June 2021) - Hao, Menggeng; Dun, Rongmin; Su, Yumiao; He, Lei; Ning, Fandi; Zhou, Xiaochun; Li, Wenmu
Abstract : The concept of metal cofactor was utilized in fabricating superior ORR electrocatalysts for fuel cells and metal–air batteries. Abstract : The nature of many highly efficient catalytic reactions catalyzed by metallocofactors is inspiring. Herein, the concept of metal cofactor was utilized in the in situ fabrication of multiple metal and heteroatom self-doped porous carbonaceous electrocatalysts. The sustainable biomass legume root nodules that contain nitrogenase were used as single precursors, and the specific surface area of the as-prepared catalyst could reach 1835 m 2 g −1 by the activation of ZnCl2 during high-temperature pyrolysis processes. The self-doped biomass-derived catalyst exhibits an outstanding oxygen reduction reaction (ORR) electrocatalytic performance with half-wave potentials ( E 1/2 ) of 0.723 V and 0.868 V ( vs. RHE) in 0.1 M HClO4 and 0.1 M KOH solution, respectively. It is worth noting that E 1/2 of the catalyst even outperforms 25 mV to that of Pt/C ( E 1/2 = 0.843 V) in alkaline electrolytes. This performance is also markedly better than that of most other reference catalysts, which is based on codoped additional transition metals or heteroatoms with biomass-derived carbonaceous materials. The catalyst also delivers promising fuel cell performance in both low-temperature air-breathing polymer electrolyte membrane fuel cells (PEMFCs) and Zn–air batteries. The role of Mo atoms from the iron-molybdenum cofactor in the as-prepared biomass-derived catalyst toward ORRs is discussed herein. This study is expected to inspire exploration and design of appropriate doping structures and compositions to develop highly active and renewable biomass-derived catalysts in diverse application fields.